2012
DOI: 10.1007/s00114-012-0942-0
|View full text |Cite
|
Sign up to set email alerts
|

Neanderthal medics? Evidence for food, cooking, and medicinal plants entrapped in dental calculus

Abstract: Neanderthals disappeared sometime between 30,000 and 24,000 years ago. Until recently, Neanderthals were understood to have been predominantly meat-eaters; however, a growing body of evidence suggests their diet also included plants. We present the results of a study, in which sequential thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS) and pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) were combined with morphological analysis of plant microfossils, to identify material entrapped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
263
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(280 citation statements)
references
References 59 publications
4
263
0
13
Order By: Relevance
“…), strawberry tree fruit (Arbutus unedo) and pine nuts (Pinus spp.). Furthermore, other studies have also indicated that plants were important parts of Neanderthal diets not only in southernmost parts such as at Gorham's Cave in Gibraltar (Barton et al, 1999), but even in northern parts of Spain (Hardy et al, 2012). Therefore, plant foods may have been especially important in Neanderthal diets in southeastern Iberian refugia.…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 97%
“…), strawberry tree fruit (Arbutus unedo) and pine nuts (Pinus spp.). Furthermore, other studies have also indicated that plants were important parts of Neanderthal diets not only in southernmost parts such as at Gorham's Cave in Gibraltar (Barton et al, 1999), but even in northern parts of Spain (Hardy et al, 2012). Therefore, plant foods may have been especially important in Neanderthal diets in southeastern Iberian refugia.…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 97%
“…Table 1 shows the archaeological time periods referred to in this article. provided evidence of plant use in archaeological contexts, for example: agricultural beginnings and plant domestication [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]; hominin and pre-agricultural human diet and ancient technologies [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]; prehistoric chimpanzee food processing and diet [54]; environmental reconstruction [55]. Table 1 shows the archaeological time periods referred to in this article.…”
Section: Starch As An Archaeological Toolmentioning
confidence: 99%
“…Starch has been found in samples of dental calculus ranging from Lower Palaeolithic hominins to Victorians [41][42][43][44][45][46][47], including from sources as diverse as Norse Shetland (Scotland), pre-Mesolithic Sudan [44], from chimpanzees [56] early Balkan agricultural populations [81] and from tropical environments [53,82]. Recovery of data on the use of plants, particularly for the early stages of the Palaeolithic, is very limited [83].…”
Section: Dental Calculusmentioning
confidence: 99%
“…Phytoliths from edible plants have been recovered from sediments in several Near Eastern Neanderthal sites (Henry et al, 1996(Henry et al, , 2004Albert et al, 1999Albert et al, , 2000Rosen, 2003). More direct evidence for Neanderthal use of plants comes from studies of residues on stone tools from several sites in France (Hardy and Moncel, 2011;Hardy et al, 2013), and from the study of residues in dental calculus from El Sidron, Spain (Hardy et al, 2012). However, none of these studies have documented Neanderthal plant use across their range of environments and many are limited in their application, either providing only indirect evidence of plant use (plant remains in sediments) or giving limited or no information about which exact species were consumed (tool and tooth residue analysis).…”
Section: Introductionmentioning
confidence: 99%